A Fractional-Order Leslie-Gower Model with Fear and Allee Effect - Adin Lazuardy Firdiansyah; Dewi Rosikhoh (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2023)
In this manuscript, we investigate the dynamics behavior of a fractional-order Leslie-Gower model by considering fear effect in the prey and Allee effect in predators. Firstly, all possible equilibrium points are analyzed by identifying the conditions of their existence and local stability. Here, we find four equilibrium points, where two local stable points and two unstable points. Furthermore, we also investigate the stability changing caused by Hopf bifurcation when the order of derivative changes. Finally, we perform several simulations to support our analysis results.